Everything you always wanted to know about inventors (but never asked): Evidence form the PatVal-EU survey - Paola Giuri; Myriam Mariani (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
From a survey of the inventors of 9,017 European patents, this paper provides new information about the characteristics of European inventors, the sources of their knowledge, the importance of formal and informal collaborations, the motivations to invent, and the actual use and economic value of the patents.
Keywords: 330; Erfindung; Patent; EU-Staaten